DEMOGRAPHIC BONUS SITUATION AS A SOLUTION ECONOMIC GROWTH USING THE COBB-DOUGLASS PRODUCTIVITY APPROACH METHOD IN MEDAN LABUHAN DISTRICT - Permadi, Mei Yusmansyah; Sijabat, Lastri Putri BR; Ruslan, Dede; Sari, Raina Linda (Politeknik Negeri Bengkalis, 2024)
The high population is not a reason, as a factor causing the increased burden on the government to provide subsidies in various formal and non-formal sectors. Still, the high population can be used as an opportunity for the government to carry out various positive economic activities, such as increasing the standard of living. Community life through growing training for productive workers in the field of entrepreneurship, training to become an entrepreneur both in cities and in rural areas, so, in this case, we support government activities to continue to race to improve the standard of living of the community which in the end can increase per capita income. The Medan Labuhan community has activities in the coastal area that are the center of their economic activities. One unique reason we focused our research on this sub-district is that according to statistical data for the city of Medan, the productive age in this sub-district is very high, above 60% of the total population of Medan city. Method The research used is the population; in this research, people of productive age live in the Medan Labuhan sub-district. The sampling technique used is nonprobability sampling, namely a sampling technique where not all members/elements of the population have the same chance of being sampled. The sampling location itself was the Medan Labuhan District location.Keywords: Â Population, Productive Age, Population, Labor